Effect of prophylactic salpingectomy on ovarian function in premenopausal women in tertiary referral center - Abdel Dayem, Tamer M.; Badawy, Amira M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Epithelial ovarian cancers (EOCs) are the most common cause of death from gynaecological malignancy. Serous ovarian carcinomas represent (68%) of Epithelial ovarian cancers, they are further divided into low-grade (type I) and high-grade (type II) serous ovarian carcinomas. There has been increasing evidence that fallopian tubes are considered the most important site of origin of pelvic high grade serous carcinoma. Salpingectomy is thought to be effective in reducing ovarian cancer risk in the future and prolonging average life expectancy, however, there are some concerns regarding ovarian function after elective salpingectomy in premenopausal women. The current study was carried out to assess the effect of salpingectomy on ovarian function in premenopausal women. Methods: 60 premenopausal cases were recruited and subjected to open abdominal hysterectomy without oophorectomy (for benign indications). Included cases were below 45 years, with documented active ovarian functions. Cases with genital malignancy, ovarian gross pathology and suspected or known ovarian failure were excluded. Cases were randomly allocated to one of two groups; group-A (where salpingectomy was performed), and group-B (where salpingectomy was not done). For all patients, ovarian functions were assessed prior operation, and at one and three months after operation using serum anti-Mullarian hormone (AMH) as well as early follicular antral follicular count (AFC), serum follicle stimulating hormone (FSH) and serum oestradiol (E2). Results: The mean pre-operative AFC, AMH, FSH, and E2 levels showed no significant changes after operation at one and three months postoperative follow up in both studied groups, denoting preserved ovarian function in both groups. Conclusions: Prophylactic salpingectomy is a safe and simple procedure that has no effect on ovarian reserve or function when performed in premenopausal women.